PENGARUH MODERNISASI ADMINISTRASI PERPAJAKAN DAN ROTASI PEKERJAAN TERHADAP KINERJA ACCOUNT REPRESENTATIVE DENGAN MEDIASI MOTIVASI PADA KANTOR PELAYANAN PAJAK MADYA SEMARANG - Faris, Ahmad; Budiati, Yuli; Indarto; Savitri, Fania Mutiara (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The Directorate General of Taxation is the agency responsible for managing state revenues through Service Offices in each region. Employees who work in tax service offices are required to perform well for the benefit of the agency. This research functions to analyze the relationship between modernization of tax administration and job rotation on the performance of the Account Representative (AR) of the Madya Semarang Tax Service Office (KPP) with Motivation as a mediation variable.This research uses quantitative approach that use questionnairy to collect the necessary data. The sample in this study was 48, obtained through the census method. The analysis used to process the data is path analysis with SmartPLS software. The results show that whether the presence or the unpresent of Tax Administration Modernization or not, ARs are still required to perform according to the standards set by the agency and are still required to work optimally after receiving the job rotation decision. Modernization of Tax Administration can increase AR motivation. AR motivation tends to be stable after employees are rotated to a new place, but high motivation can increase AR performance significantly. The findings in this research show that optimal Tax Administration Modernization can improve AR performance supported by high AR motivation.